Pengembangan dan Evaluasi Sistem Presensi Pegawai dengan Data Geolocation Menggunakan Metode Prototipe - Ariq Cahya Wardhana; Ananda Rifkiy Hasan; Teguh Rijanandi (JURIKOM (Jurnal Riset Komputer), 2022)
The Ma'arif NU Ajibarang Education Organizing Foundation (YYPMNU) is a foundation engaged in education in the Ajibarang area. There are 4 types of UPT operating under the auspices of the foundation, including SMK Ma'arif NU 1 Ajibarang, SMK Ma'arif NU 2 Ajibarang, STIKES Ibnu Sina Ajibarang, and Modern Islamic Boarding School Ibnu Sina Ajibarang. The management of the foundation's personnel attendance has been carried out by utilizing information technology but it is still not effective and efficient because the presence using fingerprints causes long queues when they come to work, so it is necessary to develop an employee attendance system that can be accessed online by all employees without having to queue. The employee attendance system has been successfully developed based on Responsive Web Apps (RWA) which features presence location coverage between employees and UPT locations using geolocation data available on employee smartphones. The results of the performance evaluation of the employee attendance system using google lighthouse resulted in an average performance of 41.5.